2018
DOI: 10.1073/pnas.1718804115
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and engineering of a plastic-degrading aromatic polyesterase

Abstract: SignificanceSynthetic polymers are ubiquitous in the modern world but pose a global environmental problem. While plastics such as poly(ethylene terephthalate) (PET) are highly versatile, their resistance to natural degradation presents a serious, growing risk to fauna and flora, particularly in marine environments. Here, we have characterized the 3D structure of a newly discovered enzyme that can digest highly crystalline PET, the primary material used in the manufacture of single-use plastic beverage bottles,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
793
4
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 795 publications
(832 citation statements)
references
References 66 publications
(89 reference statements)
28
793
4
7
Order By: Relevance
“…To get insights into the molecular mechanism of PETase, solving high-resolution crystal structure of the enzyme is of vital importance. Additional remote substrate-binding subsites have been proposed by molecular docking [10,12]. In a recent study, a number of PET hydrolase candidates were identified via searching homologous sequences from environmental metagenomes [23].…”
Section: Future Prospectsmentioning
confidence: 99%
See 3 more Smart Citations
“…To get insights into the molecular mechanism of PETase, solving high-resolution crystal structure of the enzyme is of vital importance. Additional remote substrate-binding subsites have been proposed by molecular docking [10,12]. In a recent study, a number of PET hydrolase candidates were identified via searching homologous sequences from environmental metagenomes [23].…”
Section: Future Prospectsmentioning
confidence: 99%
“…Significantly, I. sakaiensis secretes a unique cutinase-like enzyme, later dubbed PETase, to hydrolyze PET to bis(2-hydroxylethyl) TPA (BHET), mono(2-hydroxyethyl) TPA (MHET), and TPA ( Fig. Here, we summarize the most recent studies of crystal structures of PETase and its complex with substrate/product analogs reported by ourselves and other groups [9][10][11][12][13]. Under physiological conditions (30°C, pH 7.0), the enzyme is 5.5-to 120-fold more efficient than previously reported PET-hydrolyzing homologs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In April 2018, a paper in the Proceedings of the National Academy of Sciences described an engineered enzyme that can break down polyethylene terephthalate-commonly known as PET-in the water [11]; after an earlier discovery of a PET-degrading bacterium by Japanese scientists [12]. In April 2018, a paper in the Proceedings of the National Academy of Sciences described an engineered enzyme that can break down polyethylene terephthalate-commonly known as PET-in the water [11]; after an earlier discovery of a PET-degrading bacterium by Japanese scientists [12].…”
Section: Solving the Problemmentioning
confidence: 99%